The Problem of Correlation Between the Criminal Policy Humanization and the Concept of Justice at Imposing Criminal Penalties in the Republic of Kazakhstan - MASSALIMKYZY, Meruyert (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
The article raises the problem of unjustified humanization of criminal legislation and the practice of imposing a punishment. Imposing a punishment as a legal category has been extensively studied in the works of national and foreign scholars specializing in criminal law. However, despite the importance of this institution both for the convict and for the society as a whole, this penal institution remains one of the most problematic ones. The existing conflict between the current criminal policy humanism and the concept of social justice in criminal legislation, the adequacy of a punishment to the social danger of the offense being a part thereof, makes enormous harm to all law enforcement activities. It also causes negative response in the society, thus reasonably attracting a heightened attention of criminologists and experts in criminal law and procedure. The purpose of this work, as the author sees it, is trying to find feasible solutions to one of the most urgent problems of imposing a punishment. Attention is drawn to the fact that the concept of humanism has two aspects and implies, first of all, the protection of interests of law-abiding citizens. The author considers topical issues concerning the observance of the rights of victims through the solution one of the main tasks of criminal law, namely: to restore social justice by imposing a proportionate criminal punishment. Certain provisions of the theory of criminal punishment, as well as the practice of imposing punishment by the court, are studied here. Insufficient development of norms in the current criminal legislation can create problems in law enforcement, which, in turn, can lead to a significant violation of the victims’ rights. The author makes recommendations that can contribute to the improvement of the penal system consistent with the principle of humanism, considering the interests of the victims.